(untitled) (Global Journal of Management and Business Research, 2022)
The traditional agency conflict between shareholders and managers reflects the existence of a control body within companies. Thus, the Board of Directors, because of its efficiency, can be used to defend the interests of shareholders. This leads us in the context of this research to focus on the analysis of the influence of the dilution of ownership on the effectiveness of the board, more specifically in terms of disciplinary control of managers. In view of the importance of the board of directors in corporate governance, the purpose of this work is to attempt to demonstrate through a hypothetico-deductive research, the existing relationship between the dilution of ownership and the disciplinary control of the manager. Within companies. The result obtained on a sample of 61 companies confirms the presupposed link between these two groups of variables and suggests the need for companies to engage in a truly proactive approach in terms of dilution of ownership.